PERAN PEMERINTAH DAERAH DALAM PENANGANAN KONFLIK ANTAR WARGA DI KABUPATEN KOLAKA UTARA - hidayat, taufik (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2017)
Indonesia is basically a plural and multicultural country of social and cultural aspect especially in North Kolaka Regency. Differences in that aspect result in potential weaknesses that threaten national disintegration The conflict that occurred in North Kolaka District originated from the sexual harassment case originated from personal conflict and became communal conflict between residents. Based on that, the author aims to describe and explain the role of local government in handling conflicts among residents in North Kolaka District as well as supporting factors and inhibiting the role of local government in solving conflicts among residents in North Kolaka District. The type of research is qualitative method with qualitative descriptive type. The data source consists of primary data source and secondary data. Technique of collecting data is done through observation and interview. The research informants consisted of local government, sub-district and village administration, and several community figures. Data analysis technique is descriptive qualitative analysis expressed in the form of questions, responses and interpretations obtained from observation and direct interview. The results show the role of local government in handling conflict between citizens through conciliation, mediation and conflict transformation. Mediation is the dominant effort done by local government in handling conflict. Factors supporting the role of local government, namely the Standing Procedure on the handling of social conflicts and the mapping of conflict prone areas. The inhibiting factor of local government's role is the lack of budgetary support for the empowerment of FKDM at the kecamatan level as well as the quantity of police officers whose numbers are very small